Trends of Marshall Mix Design Practices in Nepal: A Perspective on Compliance with Standard Specification of Road and Bridge Work 2016 Section 1309 and Fuller’s Maximum Density Gradation - Giri, Moti Ram; Tamrakar, Gautam Bir Singh (International Journal on Engineering Technology, 2024)
This comprehensive study delves into the minute details of Marshall Mix Design practices in Nepal, specifically examining their compliance with Section 1309 of the Standard Specification for Road and Bridge Works 2016 (SSRBW 2016). The research utilized robust secondary data collection from diverse sources, including laboratories, projects, and construction sites, enhancing the dataset's utility and uniqueness. Compliance checks against SSRBW 2016 standards indicated satisfactory performance in stability and flow but highlighted concerns in the Marshall and Filler-Binder Ratio. For the Marshall Quotient, only 82% and 76% and for the Filler-binder ratio, only 61% and 38% of mix designs of gradation type I and type II respectively, followed the standard specified in SSRBW 2016, indicating tender mix design practice in Nepal. Furthermore, the study employs statistical analyses to scrutinize critical parameters, including Root Mean Square Error (RMSE), shedding light on significant disparities in mid-point gradation and sample mean of the dataset. It also investigates the compliance of mix designs with Fuller's ideal gradation for maximum density, emphasizing the significance of aggregate gradation in pavement performance. The evaluation of gradation at 0.45, 0.5, and 0.55 exponents extends to the interplay of volumetric properties, emphasizing the need for refined gradation specifications to enhance the durability and overall performance of asphalt mixtures in the Nepalese context. In this study, RMSE results offer a quantitative measure of the percentage discrepancies between observed gradation and anticipated values of Fuller’s gradation, resulting in RMSE values computed at 3.37%, 4.77%, and 6.74% for percentage passing in the mid-point grade of type I, and 8.23%, 10.89%, and 13.30% for mid-point grades of type II. This analysis provides a clear understanding of the deviation from Fuller's maximum density gradation. The study concludes with actionable recommendations for practitioners and policymakers, aiming to optimize mix designs gradation of Section 1309 of SSRBW 2016 for asphalt pavements in Nepal.